1976
DOI: 10.1093/infdis/133.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Exotoxin in Mice: Histopathology and Serum Enzyme Changes

Abstract: The histopathology and serum levels of mice inoculated intravenously with Pseudomonas aeruginosa exotoxin were studied. The toxin exerted a marked effect on the liver but elicited no demonstrable microscopic changes in other organs. The microscopic lesions caused in the liver by a single injection of two 50% lethal doses (LD50) of toxin (2.3 mug) were characterized by necrosis, cellular swelling, and fatty change within 4--8 hr and near total hepatocellular necrosis at 48 hr. Hepatic necrosis was accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 9 publications
3
20
0
Order By: Relevance
“…These findings are similar to the previous observation of PEA-induced hepatotoxicity in mice [16]. Secondly, TUNEL staining appeared to be the earliest feasible indicator detecting hepatotocyte apoptosis.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings are similar to the previous observation of PEA-induced hepatotoxicity in mice [16]. Secondly, TUNEL staining appeared to be the earliest feasible indicator detecting hepatotocyte apoptosis.…”
Section: Discussionsupporting
confidence: 90%
“…In the 30 µg/kg group, mortality was 37% at 48HPE but 25% at 60 HPE, suggesting that the critical hepatotoxicity effect might have saturated by 48 HPE. In comparison with various doses for inducing death in mouse study (85 [20], 300 [4,5], and 500 [15] µg/kg PEA in C57BL/6; 85 [18)] and 300 [26] µg/kg in BALB/c; 115 µg/kg [16] in Swiss; and 600 µg/kg [1] in Mttp ∆/∆ (background: 50% 129/SvJae and 50% C57BL/6)). These were 8-fold differences among the same species animals that appeared to be confusing to researchers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to other studies, we found no correlation among liver disease and lung function or bacterial colonization, implying that bacterial toxin production had no great impact on liver damage. 45,46 The prevalence of BLD was surprisingly constant despite changes of treatment modalities during the long study period. The development of more efficient pancreatic enzymes, fat emulsion therapy given more or less regularly, and new intravenous antibiotics directed against P. aeruginosa have improved nutrition and lung function and this might be 1 possible factor behind the low number of patients with severe liver disease despite the increasing median age of our population.…”
Section: Discussionmentioning
confidence: 97%